2006
DOI: 10.1017/s1930297500000346
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Risk Assessment: Why do Women Take Fewer Risks than Men?

Abstract: Across many real-world domains, men engage in more risky behaviors than do women. To examine some of the beliefs and preferences that underlie this difference, 657 participants assessed their likelihood of engaging in various risky activities relating to four different domains (gambling, health, recreation, and social), and reported their perceptions of (1) probability of negative outcomes, (2) severity of potential negative outcomes, and (3) enjoyment expected from the risky activities. Women’s greater percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(99 citation statements)
references
References 18 publications
3
57
0
7
Order By: Relevance
“…Quite a bit of research has indicated that women are more risk averse than men (e.g., Byrnes et al, 1999;Carr & Steele, 2010;Croson & Gneezy, 2009;Dwyer, Gilkeson & List, 2002;Eriksson & Simpson, 2010;Finger & Weber, 2011;Harris, Jenkins & Glaser, 2006). General acceptance of this conclusion may be potentially problematic because it becomes part of gender discussions on topics such as competitiveness, management style, labor markets and investment success (Booth & Nolen, 2012;Eckel & Grossman, 2008;Kahan, Braman, Gastil, Slovic & Mertz, 2007;Kristof, 2009;Wieland & Sarin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Quite a bit of research has indicated that women are more risk averse than men (e.g., Byrnes et al, 1999;Carr & Steele, 2010;Croson & Gneezy, 2009;Dwyer, Gilkeson & List, 2002;Eriksson & Simpson, 2010;Finger & Weber, 2011;Harris, Jenkins & Glaser, 2006). General acceptance of this conclusion may be potentially problematic because it becomes part of gender discussions on topics such as competitiveness, management style, labor markets and investment success (Booth & Nolen, 2012;Eckel & Grossman, 2008;Kahan, Braman, Gastil, Slovic & Mertz, 2007;Kristof, 2009;Wieland & Sarin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another viable solution would be to use different risk elicitation tasks to extract a common risk factor (R), thereby increasing ac-curacy and reducing measurement error (Frey et al, 2017). Extending this possibility, risk could be measured in a variety of domains, both to study effects in each domain and to extract a cross-domain general factor (e.g., Harris, Jenkins & Glaser, 2006).…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, cognitive capacities, and in particular executive functions, are known to decrease with age. Moreover, men may take more risks than women [44][45][46]. Hence, the effects of sex and age on the three variables of interest were analyzed individually to orient the structure of random effects, using t-test and linear regression analyses, respectively.…”
Section: Discussionmentioning
confidence: 99%